2013
DOI: 10.2147/ijgm.s45004
|View full text |Cite
|
Sign up to set email alerts
|

Age group athletes in inline skating: decrease in overall and increase in master athlete participation in the longest inline skating race in Europe – the Inline One-Eleven

Abstract: BackgroundParticipation and performance trends in age group athletes have been investigated in endurance and ultraendurance races in swimming, cycling, running, and triathlon, but not in long-distance inline skating. The aim of this study was to investigate trends in participation, age, and performance in the longest inline race in Europe, the Inline One-Eleven over 111 km, held between 1998 and 2009.MethodsThe total number, age distribution, age at the time of the competition, and race times of male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The present findings in participation and performance in these mountain marathoners competing in the ‘Jungfrau Marathon’ might be specific for Switzerland. Teutsch et al ( 2013 ) investigated participation and performance trends in age group inline skaters competing between 1998 and 2009 in the longest inline race in Europe, the ‘Inline One-Eleven’ over 111 km, which was also held in Switzerland. During the 12-year period, overall participation increased until 2003 but decreased thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings in participation and performance in these mountain marathoners competing in the ‘Jungfrau Marathon’ might be specific for Switzerland. Teutsch et al ( 2013 ) investigated participation and performance trends in age group inline skaters competing between 1998 and 2009 in the longest inline race in Europe, the ‘Inline One-Eleven’ over 111 km, which was also held in Switzerland. During the 12-year period, overall participation increased until 2003 but decreased thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The relative participation in athletes younger than 40 years old decreased while relative participation increased for athletes older than 40 years. The race times of the best female and male skaters stabilized across years (Teutsch et al 2013 ). In the 120-km ultra-endurance mountain bike race the ‘Swiss Bike Masters’ held in Switzerland from 1995 to 2009, similar findings were reported (Gloor et al 2013 ; Haupt et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Local reasons can also explain the decrease in participation, since a decrease in participation has also been documented for other sports disciplines held in Switzerland in the last decades. The number of participants in specific line skating races such as 'Inline 111' [27] and specific mountain bike cycling races such as 'Swiss Bike Masters' [26] also decreased. More studies are needed to investigate trends in participation in specific races and/or sports disciplines in specific regions and/or countries.…”
Section: Decrease In Male Participation After 1984mentioning
confidence: 99%
“…An increase in participants has been reported mainly due to an increase in female and age group athletes for the Duathlon World Championship [25], for 'Ironman Switzerland' [24], for half-marathoners but not for marathoners [16]. However, in recent decades, world-famous races with a pioneering character such as one of the first mountain bike ultramarathons in the world, the 'Swiss Bike Masters' [26], and the longest inline skating race, the Inline 111' [27], have disappeared. Furthermore, a study investigating master athletes in the '100 km Lauf Biel' showed a decrease in participation of younger age group runners [28].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a considerable increase in participation of master athletes and in several age groups athletes also improved performance in different endurance sport disciplines such as marathon (Anthony et al 2014 ; Jokl et al 2004 ) and ultra-marathon running (Jampen et al 2013 ; Rüst et al 2013 ; Zingg et al 2013 ) ultra-cycling (Shoak et al 2013 ), long-distance triathlon such as Ironman triathlon (Lepers et al 2013 ; Stiefel et al 2013 , 2014 ) and Triple and Deca Iron ultra-triathlon (Knechtle et al 2012 ), long-distance inline-skating (Teutsch et al 2013 ) and ultra-mountain biking (Haupt et al 2013 ). Although large cross-sectional studies in swimming already investigated changes of age, performance (König et al 2014 ) and sex differences (Wild et al 2014 ) in World Championships, cross- sectional studies investigating participation and performance trends of master backstroke swimmers are missing.…”
Section: Introductionmentioning
confidence: 99%